2015
DOI: 10.1007/s00595-015-1208-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between histological invasiveness and the computed tomography value in pure ground-glass nodules

Abstract: PurposeThe purpose of this study was to evaluate the correlation between histological invasiveness and the computed tomography (CT) value and size in pure ground-glass nodules (GGNs) to determine optimal “follow-up or resection” strategies.MethodsBetween 2001 and 2014, 78 resected, pure GGNs were retrospectively evaluated. The maximum diameter and CT value of pure GGNs were measured using a computer graphics support system.ResultsAll GGNs with a maximum diameter ≤10 mm and CT value ≤−600 Hounsfield units (HU) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
42
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 25 publications
8
42
3
1
Order By: Relevance
“…Because integers are more convenient in clinical practice, we used published cutoff values in our univariable and multivariable analyses (age > 55 years, maximal diameter > 1 cm, CT density > −600 HU). In the present study, model 2 suggested that maximal and mean diameters could reliably and independently distinguish IACs in patients with pGGNs with diameters of < 3 cm; this nding was consistent with reported literature [11,15].In the current study, a tumor diameter of > 10 mm was a signi cant independent predictor of IAC; however, that result is not readily apparent from the scatter plot shown in Figure 3. The best predictor of IAC may be a diameter of > 20 mm, because only one of the pre-IACs shown in Figure 3 had a diameter > 20 mm.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Because integers are more convenient in clinical practice, we used published cutoff values in our univariable and multivariable analyses (age > 55 years, maximal diameter > 1 cm, CT density > −600 HU). In the present study, model 2 suggested that maximal and mean diameters could reliably and independently distinguish IACs in patients with pGGNs with diameters of < 3 cm; this nding was consistent with reported literature [11,15].In the current study, a tumor diameter of > 10 mm was a signi cant independent predictor of IAC; however, that result is not readily apparent from the scatter plot shown in Figure 3. The best predictor of IAC may be a diameter of > 20 mm, because only one of the pre-IACs shown in Figure 3 had a diameter > 20 mm.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have analyzed relationships between CT features of pGGNs and pathological type [15][16][17][18]. However, to the best of our knowledge, no published study has identi ed predictors of lung IACs in pGGNs by analyzing their clinical and imaging characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They addressed the CT characterization of resected pGGN adenocarcinoma in the three categories of stromal infiltration: adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA), and invasive adenocarcinoma (IAC) (3). This is one of the few reports in non-Asian population (only 10% of patients were Asian), compared to a majority of Asian studies related to the quite common surgical approach to pGGN ( Table 1) (4)(5)(6)(7)(8)(9)(10)(11)(12). Notably, the reported results detail the CT appearance through the continuum of adenocarcinoma invasiveness and show the direct association between radiological size of pGGN and conspicuity of stromal invasion on histological specimen (e.g., number and size of invasive foci).…”
mentioning
confidence: 99%